Communication pattern and decision making in Parti Keadilan Rakyat (the People’s Justce Party) Malaysia: Phenomenography approach - Priyowidodo, Gatut; Abu Bakar, Hassan; Mustaffa, Che Su (2011)
The purposes of the research were first, to identify communication pattern in Parti Keadilan Rakyat (the People’s Justice Party).And second, to identify the implementation of the decision-making in Parti Keadilan Rakyat (the People’s Justice Party).This study utilized a phenomenographical approach (qualitative method) and Nvivo analysis to reveal the conceptions of communication pattern and decision making in the People’s Justice Party (PKR). Research findings are; 1) the communication pattern in the People’s Justice Party covers the formal and informal communication pattern.Formal is upward and downward communication pattern.Informal included horizontal communication, cross channel/diagonal communication and grapevine communication.2.The process of decision making is determined by three factors context, experience and authority.Meanwhile, limitation of the study is, in general, qualitative research.First, this study is put on the interview.This means that researchers can in no way confirm that the information in the form of the story is true experience or manipulative.Human attitudes and actions can always be changed.Second, researchers have limitations in data access of the informant.Third, interpretation of data depends on the researcher.Fourth, informants were selected only from some members and leaders and thus cannot be claimed as representing the communication patterns implemented by everyone.